2018
DOI: 10.15171/jlms.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Is Holmium Laser an Appropriate Modality to Treat Genital Warts?

Abstract: Introduction: Genital warts in young adults aged 18-28 years are very common. Several approaches are routinely used in the treatment of warts, viz., medical treatment (podophyllin and trichloroacetic acid), conventional surgery (excision or electrocautery), cryotherapy, and laser treatment. Because of high recurrence rates after treatment, complications and long duration of treatment, newer modalities have been developed. One of these newer methods is laser, which has been used in several urologic diseases. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…18,27,36,37 In a recent retrospective study comparing the Holmium laser, cryotherapy, conventional surgery and podophyllin, Ghiasy et al found that the Holmium laser was the best treatment of genital and meatal warts, with the highest clearance rate (92.2%) through a single session and the lowest recurrence rate (14.3%), compared to other treatments. 25 However, the follow-up period of this study was only 6 months, and the patients treated by the holmium laser were 39. Yang et al 27 reported the results from a large cohort study in which 1500 patients with genital and urethral warts were treated using the Holmium laser.…”
Section: Discussionmentioning
confidence: 86%
“…18,27,36,37 In a recent retrospective study comparing the Holmium laser, cryotherapy, conventional surgery and podophyllin, Ghiasy et al found that the Holmium laser was the best treatment of genital and meatal warts, with the highest clearance rate (92.2%) through a single session and the lowest recurrence rate (14.3%), compared to other treatments. 25 However, the follow-up period of this study was only 6 months, and the patients treated by the holmium laser were 39. Yang et al 27 reported the results from a large cohort study in which 1500 patients with genital and urethral warts were treated using the Holmium laser.…”
Section: Discussionmentioning
confidence: 86%
“…Today, the laser has an excellent application in urologic diseases. [22][23][24] Endoscopic laser lithotripsy (LL) is frequently used to manage patients with urolithiasis. 8,25 A number of lasers have been used for LL, of which the Ho:YAG has become one of the most frequently used one.…”
Section: Discussionmentioning
confidence: 99%
“…12 Today, Ho: YAG lasers broadly used in urological surgery include urolithiasis, [13][14][15] benign prostatic hyperplasia, 16 urinary tract strictures, 17 bladder malignancies or lesions of the external genitalia. 10,18 IU is a kind of transurethral intervention in which the stricture is incised by cold-knife or thermal energy incision. 4 The dominant benefits of laser treatments consist of decreased blood loss and hospital admission.…”
Section: Discussionmentioning
confidence: 99%